Features of Glucose Homeostasis and Blood Lipid Spectrum in Patients with Nonalcoholic Fatty Liver Dis ease Depending on the Obesity Degree - Korniichuk I.; Khukhlina O.; Vivsyannuk V.; Yatskevych O.; Kovalska І. (Львівський клінічний вісник)
Introduction. The increase of the number of obese patients is growing steadily not only in Ukraine but also in the world. In the economically developed countries, almost 50.0 % of the population are overweight, including 30.0 % obese. Among the ablebodied population of Ukraine, overweight and obesity are detected in almost 30.0 % of cases. Typical for a modern society, sedentary lifestyle, inappropriate nutrition with an increase in the number of refined products, constant psychological stress lead to an increase in the incidence of obesity among people of all ages, especially young people. WHO notes the increase in the amount of children and adolescents with overweight and obesity to 20.0 % in Europe. It has been found that childhood obesity is an important pathogenic component of obesity in adults. Among the complications of obesity, nonalcoholic fatty liver disease, the occurrence of which significantly reduces the life quality of patients, contributes to the development of glucose tolerance disorders, development and progression of hepaticcellular insufficiency. The aim of the study. To study the features of glucose homeostasis and blood lipid spectrum in patients with nonalcoholic liver disease depending on the obesity degree. Materials and methods. After obtaining a written consent for conducting the comprehensive survey in accordance with the principles of the Helsinki Declaration of Human Rights, the Council of Europe Convention on Human Rights and Biomedicine and relevant laws of Ukraine, 120 patients (62 women, 58 men, mean age 42.5 ± 3.4 years) with NAFLD and obesity were screened in a randomized manner with the preliminary stratification by the presence of NAFLD and obesity of І-ІІІ degrees. Among them, 40 patients have nonalcoholic liver steatosis (NALS), of which 20 people have I degree obesity (1a), another 20 patients II-III obesity (1b). 80 patients with nonalcoholic steatohepatitis (NASH) were examined. In all the patients the diagnosis of obesity was established: 40 patients have I degree (2nd group), 40 people II-III degree (3rd group). Groups of patients with NASH, in turn, were divided into clusters: 2a and 3a patients with NASH and the increased AST activity in blood up to 3 times higher than norm (20 people), 2b and 3b – patients, AST activity in which exceeded the upper limit of norm more than in 3 times (p < 0.05). The control group consisted of 20 practically healthy persons (PHPs) of the corresponding age and gender. Results. The obtained data testify that the lipid distress syndrome in the majority of the examined patients with NAFLD and obesity is one of the most metabolically important prerequisites for the development. The maximum increase of the dyslipidemia coefficient is observed in patients with NASH with the highest increase of AST activity in case of ІІ-ІІІ degree obesity (in 4.4 times (p < 0.05) compared to the PHP. The high degree of correlation between the IR indices and the content of cholesterol, TG, and LDL indicates the metabolic dependence of the development of NAFLD and IR: between HOMA IR and the content of TG in the blood (r = 0.88, p < 0.05), cholesterol (r = 0.85, p <0.05), LDL (r = 0.89, p <0.05), HDL (r = 0.83, p < 0.05), which proved firstly, that the lipid distress syndrome is the consequence and the leading manifestation of IR as a main component of the metabolic syndrome, and secondly, indicates a causal relationship with the development of NAFLD. Conclusions. In patients with nonalcoholic fatty liver disease comorbid with the obesity, the significant increase of the levels of postprandial glycemia, insulinemia, hemoglobin glycosylation degree and insulin resistance (HOMA IR), hypertriacylglycerolemia, hypercholesterolemia, cholesterol content in low density lipoproteins, and a lack of cholesterol content in highdensity lipoproteins, which increase directly in proportion to the degree of obesity, with the progression of NALS to NASH and the increase of the cytolytic syndrome activity in case of nonalcoholic steatohepatitis.